Study the Utilization of Biochar Derived from Sugarcane Waste to Enhance the Biogas Efficiency During the Anaerobic Digestion Process for Treating Pig Farm Wastewater: https://doi.org/10.69692/SUJMRD100199 - BUAMANYSONE, Phaeng; KHOUNVILAY, Keonakhone; XAIXONGDETH, Phenakhone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This experiment aims to study the use of biochar (Biochar, BC) from sugarcane trash through the pyrolysis process at different temperatures of 300, 400, 500, 600 and 700°C. Then add BC to the Anaerobic Digestion (AD) system of wastewater from pig farms, then analyze the characteristics of wastewater and the amount of biogas obtained before and after treatment and to study the characteristics of decomposition, the generation of biogas (Biogas) to the reduction of organic matter in wastewater (COD). From this experiment, it can be concluded that all 6 systems are producing biogas, such as: the normal system and the system with BC filling at different burning temperatures: 300, 400, 500, 600 and 700℃ in the amount of 0.4g into the system. .64, 46.13, 51.90 and 65.98% respectively. From the experiments of all systems, it is observed that the system filled with BC at a temperature of 700℃ is able to produce biogas the best because the high heating temperature will cause the electrons of the charcoal to break easily and cause more holes to be a place for microbes to grow well. A comparison of the conventional system and adding biochar with the same amount but different temperature into the sewage treatment system without using air can be concluded that the conventional system is the generation of biogas is still low efficiency and the system of adding BC at the temperature of 300, 400, 500, 600℃ in the same amount. Notice that the generation of biogas is higher in order and the filling of BC at a temperature of 700℃ is able to produce biogas higher than other systems.